Evaluating Wind Speed by WRF Model over Northern Thailand - Pakpoom Ratjiranukool (2018)
© 2017 The Authors. Published by Elsevier Ltd. The aim of this research is to estimate wind speed for northern Thailand by using a high resolution regional climate model called Weather Research Forecasting (WRF) version 3.7. The model was forced by the Community Climate System Model version 3 (CCSM3) which is a coupled climate model for simulating global climate system. The period of study was 5 years interval (2000-2004). The spatial wind speed distribution was analyzed seasonally by using the Grid Analysis and Display system (GrADS). The 5-year averaged wind speed simulations were compared to 13 station observation data sets provided by the Thai Meteorological Department (TMD). The statistical analysis presented Root mean square error (RMSE) and correlation.